Exporting and the business-to-business market : Alibaba.com - Baack, Daniel W., (SAGE knowledge. Cases., 2016)
This case study examines the Chinese business-to-business website Alibaba.com and how it came to hold a 69% market share in the Chinese business-to-business e-commerce market. The company was established after its founder, Jeffrey Ma, noticed a gap in the market for Chinese business to export their goods and services to global importers.